Antecedents of absorptive capacity in the development of circular economy business models of small and medium enterprises. (10th October 2021) - Marrucci, Luca; Iannone, Fabio; Daddi, Tiberio; Iraldo, Fabio
Abstract: Most firms, especially small and medium enterprises (SMEs), find it difficult to integrate circular economy strategies within their business models. Moreover, there is a lack of research on approaches for the successful implementation of circular economies in SMEs in the field of manufacturing. To fill this gap, we investigate the antecedents of absorptive capacity in successful circular economy business cases using a qualitative multiple‐case study. Focusing on the horticultural sector, we interviewed six Italian SMEs using NVivo 12 for the analysis. The data were then classified into first‐order and second‐order categories and then sorted into absorptive capacity dimensions. Our results highlight the significant contribution provided by absorptive capacities to the circular economy in SMEs. We highlighted three antecedents for each absorptive capacity dimension and explored their key concepts. Our study contributes to the academic literature on the links between absorptive capacity and corporate sustainability by providing insights into the role of acquisition, assimilation, transformation and exploitation capabilities in the successful implementation of circular economy practices.